Karnataka Draft Annual Plan 1987- 88 Government of Karnataka Planning Department - Planning Commission (Planning Commission, 1986)
Any review of the State's Annual Plan of 1986-87 on the basis of the progress registered during April-September of the year is best with constraints of inadequate data and uncertainty in the second half of the annual plan period. It will be very difficult to make precise projections of the possible attainment of the goals set for the annual plan in so far as a larger number of schemes have characteristics which call for spreading out of the schedule of implementation in a progressive manner so as to be capable of showing satisfactory results more and more in the third and final quarters of the year. While the condition of the kharif crops may be assessed, the prospects of rabi and summer elude any reasonable forecast. Under these circumstances what is presented in this chapter has to be taken as a highly tentative review of the Annual Plan of 1986-87.
Government of Karnataka Planning Department